Prótese total removível convencional e implanto retida com carga imediata: função mastigatória e condição nutricional - Borges, Tânia de Freitas (2007)
The aim of this study was to verify masticatory performance, masticatory ability, nutritional status, satisfaction with denture, quality of life related to oral health, as well as the association between variables. Sixteen individuals from 30 to 76 years of age, of both genders, wearers of bimaxillary mucosupported complete dentures (MSD), were assessed before, immediately, three and six months after conversion of the mandibular denture into a mucosupported and implant retained denture (IRD), improving its retention and stability by means of two implants in the mandibular bone and a bar/clip system. Masticatory performance was analyzed using the Optocal food simulator test, masticated for 20 and 40 cycles. Masticatory ability by a questionnaire and the Visual Analogue Scale (VAS). Nutritional status was assessed by means of the Mini-Nutritional Assessment (MAN) questionnaire, and blood albumin, transferrin, total cholesterol, lymphyocyte and reactive C protein analyses. Satisfaction with the denture was assessed by means of the questionnaire and EVA. The OHIP-14Br questionnaire was used to evaluate the quality of life related to oral health. To be related masticatory performance test with other tests. The data collected were submitted to statistical analysis (α = .05) by means of the Friedman, Wilcoxon, student s-t test for paired samples, student s-t test for non-paired samples, Cochran s Q and Mann-Whitney s U tests. It was observed in masticatory performance that the individuals potential for chewing Optocal improved significantly after three months of immediate conversion of the mandibular MSD to IRD. In the masticatory ability analysis by the questionnaires and EVA, there was statistically significant difference only after six months. Masticatory performance had no relation with masticatory ability. Nutritional assessment by MAN demonstrated significant improvement six months after the conversion of MSD to IRD. In the hematologic exam, there was no statistically significant difference for albumin, transferrin, total cholesterol, reactive C protein and lymphocytes in the assessments performed before, three and six months after conversion. MAN and the hematologic exams showed no relation, however, no patient was classified as undernourished by MAN, and the same could be observed from the hematologic exam. Satisfaction with the mandibular denture rose from 43.755 to 100% immediately after conversion, there being more complaint about the maxillary denture after the conversion (6.25% to 25% dissatisfaction). Quality of life related to oral health showed immediate improvement after the conversion from MSD to MSIRD, but statistically significant difference only occurred as from the three-month assessment. For the participants considered nourished by MAN, the mean of the masticatory performance index before mandibular denture conversion was 22.43%, while for those at risk for malnutrition it was 3.9%, and six months after the conversion this index rose to 33.75% and 19.93%, respectively. Satisfaction with the mandibular denture and the quality of life related to oral health presented no relation to the masticatory performance index.